1996
DOI: 10.1007/bf00403305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ingested fructose and infused glucagon on endogenous glucose production in obese NIDDM patients, obese non-diabetic subjects, and healthy subjects

Abstract: SummaryIncreased endogenous glucose production (EGP) and gluconeogenesis contribute to the patho-genesis of hyperglycaemia in non-insulin-dependent diabetes mellitus (NIDDM). In healthy subjects, however, EGP remains constant during administration of gluconeogenic precursors. This study was performed in order to determine whether administration of fructose increases EGP in obese NIDDM patients and obese non-diabetic subjects. Eight young healthy lean subjects, eight middle-aged obese NIDDM patients and seven m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 29 publications
2
25
0
1
Order By: Relevance
“…set at 0.2, G is the glucose concentration (mg/l), E is the 6,6-2 H 2 -glucose isotopic enrichment (mol% excess), and t is the time of collection (min) (16). Parameters were set assuming that kinetics for 13 C-glucose appearance in blood after ingestion of a 13 C-labeled glucose load apply to the ingestion of a 13 C-labeled fructose load as well (17).…”
Section: Obesitymentioning
confidence: 99%
“…set at 0.2, G is the glucose concentration (mg/l), E is the 6,6-2 H 2 -glucose isotopic enrichment (mol% excess), and t is the time of collection (min) (16). Parameters were set assuming that kinetics for 13 C-glucose appearance in blood after ingestion of a 13 C-labeled glucose load apply to the ingestion of a 13 C-labeled fructose load as well (17).…”
Section: Obesitymentioning
confidence: 99%
“…That reduction in EGP by 21% could occur by a starvation-induced glycogen depletion mechanism is unlikely a priori if glycogen provided only 12% of EGP at baseline in type 2 diabetes, as was concluded using the NMR method (7). A primary role for glycogenolysis as a modulating pathway over EGP in type 2 diabetes is consistent with the failure of either reducing gluconeogenesis substrate availability (with ethanol) (34) or increasing gluconeogenesis substrate availability (with fructose) (35) to alter EGP in diabetic subjects, as in healthy control subjects (33,36).…”
Section: Mp Christiansen and Associatesmentioning
confidence: 90%
“…One crucial feature before using such a triagonist in humans would be to have a well-balanced glucagon activity. Indeed, glucagon is known as a counterregulatory hormone that exerts a potent hyperglycaemic effect by increasing hepatic glucose output through the stimulation of both glycogenolysis and gluconeogenesis 9 . Some experimental data suggested that glucagon suppression or inactivation may provide therapeutic advantages over insulin monotherapy 10 .…”
Section: Wordsmentioning
confidence: 99%